The Effect of SACH and Dynamic-Response Feet on Several Kinetic Variables in Stance Phase of Running of Individuals with Unilateral Transtibial Amputees - Mehrdad Anbarian; Mohammad Hassan Modares Sabzevari; Mohammad Reza Safari; Seyed Farhad Tabatabai (Vesnu Publications, 2015)
Introduction: Receiving artificial limb, transtibial amputees are forced to use a kind of prosthetic feet to replace lost limb. Biomechanical Characteristics of unilateral transtibial amputees with various types of prosthetic feet during running have been studied. Although SACH and Dynamic-Response feet manufactured by Otto Bock are the most components used in Iran, examining function of these feet is less considered in locomotion activity .The purpose of this study was to survey the effect of SACH and Dynamic-Response feet on several kinetic variables in stance phase of running of individuals with unilateral transtibial amputees. Materials and Methods: Eight male unilateral transtibial amputees participated in this study. Each subjects running in 12 meter runway three times at a speed of 2.5 meters per second with each feet. Kistler force plate and three-dimensional motion analysis Vicon system were used to collect kinetic data and control running speed respectively. Determination the effect of feet was used ANOVA with repeated measures in normal data and Friedman test in non-normal data (P < 0.05). Results: The residual leg of individuals with unilateral transtibial amputees did not show shock absorption index (peak vertical ground reaction force during heel contact). Ground reaction force were significantly different between the SACH, Dynamic-Response and main feet (P < 0.001) that SACH feet have greater ground reaction force rather than Dynamic-Response and main feet (P < 0.001). There was no statistical difference vertical impulse between feet (P = 0.38).